Tight Junction in the Intestinal Epithelium: Its Association with Diseases and Regulation by Phytochemicals - Bonggi Lee; Kyoung Mi Moon; Choon Young Kim (Journal of Immunology Research)
The intestine plays an essential role in integrating immunity and nutrient digestion and absorption. Adjacent intestinal epithelia form tight junctions (TJs) that are essential to the function of the physical intestinal barrier, regulating the paracellular movement of various substances including ions, solutes, and water across the intestinal epithelium. Studies have shown that TJ dysfunction is highly associated with metabolic and inflammatory diseases. Thus, molecular and nutritional factors that improve TJ activity have gained attention in the pharmaceutical and medicinal fields. This review focuses on the association between TJ and diverse pathological conditions, as well as various molecular and nutritional interventions designed to boost TJ integrity.